2018
DOI: 10.3390/nu10050558
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lactose-Free Diet on the Phalangeal Bone Mineral Status in Italian Adolescents Affected by Adult-Type Hypolactasia

Abstract: Adult-type hypolactasia (ATH) is a clinical syndrome of primary lactase deficiency. A lactose-free diet is advisable to avoid the symptoms linked to the condition, but this potentially creates problems for optimal bone mineralization due to reduced calcium intake. To evaluate the effect of the lactose-free diet on the bone mineral status (BMS), we compared the phalangeal BMS of adolescents with ATH to that of peers on a normal diet. Also, we analyzed the correlations between BMS and dietary behavior, physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…Many studies in literature, including meta-analyses, have evaluated the relationship of 25(OH)D levels and BMD of children with IEM consuming protein-restricted diets (mainly phenylketonuria), and could not detect any significant correlation. [16][17][18][19][20] Moreover, in this study, no significatant relationship was detected between vitamin D levels and BMDs of patients receiving specialised diets.…”
Section: Discussioncontrasting
confidence: 68%
“…Many studies in literature, including meta-analyses, have evaluated the relationship of 25(OH)D levels and BMD of children with IEM consuming protein-restricted diets (mainly phenylketonuria), and could not detect any significant correlation. [16][17][18][19][20] Moreover, in this study, no significatant relationship was detected between vitamin D levels and BMDs of patients receiving specialised diets.…”
Section: Discussioncontrasting
confidence: 68%
“…It has been demonstrated that a daily milk consumption of 245 mL (a cup) is associated with increased body height (0.39 cm, 95% CI 0.29 to 0.48) [37]. Baldan and colleagues [38] evaluated the effect of a lactose-free diet on the phalangeal BMS in 102 LI adolescents compared to that of 102 peers on a normal diet. In particular, the time spent on a lactose-free diet (4.8 ± 3.1 years) was inversely correlated to the BMS.…”
Section: Nutritional Management In LI Patientsmentioning
confidence: 99%
“…Given the extensive and costly impact of osteoporosis, taking steps throughout life to prevent it is essential to lowering this health burden. As dietary calcium is one of the primary strategies to build and maintain strong and healthy bones, it is critical to ensure adequate calcium intake at each life stage, especially in lactose-intolerant individuals that consume less dietary calcium than their peers [4].…”
Section: Bone Health Throughout the Life Spanmentioning
confidence: 99%
“…In adolescents, a study by Baldan et al demonstrated that lactose malabsorbers who substituted regular cow’s milk with lactose-free milk showed no difference in bone mineral status as compared to controls, despite a lower calcium intake [4]. In adults, BMD was found to be lower with lactose maldigestion and lower dairy intakes [71,72,73].…”
Section: Human Studies Of Lactose Intolerance Dairy Avoidance Anmentioning
confidence: 99%